Strength on cut edge and ground edge glass beams with the failure analysis method - Stefano Agnetti (Fracture and Structural Integrity)
The aim of this work is the study of the effect of the finishing of the edge of glass when it has a structural function. Experimental investigations carried out for glass specimens are presented. Various series of annealed glass beam were tested, with cut edge and with ground edge. The glass specimens are tested in four-point bending performing flaw detection on the tested specimens after failure, in order to determine glass strength. As a result, bending strength values are obtained for each specimen. Determining some physical parameter as the depth of the flaw and the mirror radius of the fracture, after the failure of a glass element, it could be possible to calculate the failure strength of that.The experimental results were analyzed with the LEFM theory and the glass strength was analyzed with a statistical study using two-parameter Weibull distribution fitting quite well the failure stress data. The results obtained constitute a validation of the theoretical models and show the influence of the edge processing on the failure strength of the glass. Furthermore, series with different sizes were tested in order to evaluate the size effect.